PENGARUH PENGEMASAN SECARA INDIVIDU MENGGUNAKAN PLASTIK FILM REGANG TERHADAP MUTU BUAH MANGGIS SELAMA PENYIMPANAN. - S. Utama, I Made; G.M. Permana, I Dewa; G. Lidartawan, I Dewa Agung (Agrotekno; Vol. 12, No. 1 Februari 2006, 2012)
The objective of this research was to study the effect of individual sealed packaging using stretching plastic film on quality of mangoesteen fruits with harvest index 4 and 5 during storage at room temperature (28 ?b 2oC) and at 5oC. Mangosteen fruits seal-packed individually using stretching plastic film is very beneficial since the packaging could extend the shelf life and maintain the fruit quality. The fruits with harvest index of 4 were better to be sealed individually with the plastic film as their shelf life were more than 24 days compare to the fruits with harvest index of 5 of which their shelf life were 20 days at room temperature. The result shows that mangosteen fruits were very sensitive to chilling injury which was indicated by the hardening of fruit shell. It was suggested that to prolong the shelf life of mangosteen fruits, the harvesting of mangoesteen fruits should be done on harvest index 4 and packaged them with stretching plastic film individually.
Keywords: Buah manggis, pengemasan individu, plastik film regang, modifikasi atmosfer